CLINICAL AND ECHOCARDIOGRAPHIC FEATURES OF PATIENTS WITH HEART FAILURE WITH MID-RANGE EJECTION FRACTION COMPARED TO REDUCED AND PRESERVED. (April 2021) - Biolcati, Marco; Maloberti, Alessandro; Bianchi, Sofia; Giani, Valentina; Pellegrinelli, Claudia; Ceratti, Umberto; Belli, Oriana; Casadei, Francesca; Musca, Francesco; Sormani, Paola; Santambrogio, Gloria; Spano', Francesca; et al.
Abstract : Objective: The 2016 ESC guidelines classify Heart Failure (HF) according to levels of Ejection Fraction (EF) in HF with reduced EF (HFrEF, EF < 40%), HF with preserved EF (HFpEF, EF > = 50%) and the newborn HF with mid-range EF (HFmrEF, EF 40–49%). The aim of our work is to analyse clinical and echocardiographic features of patients admitted for HF when divided accordingly to their admission EF, focusing on HFmrEF. Design and method: We enrolled 192 patients hospitalized in the Internal Medicine of our hospital between January and September 2017. We collected data on clinical history, physical examination, laboratory tests, pharmacological treatment and echocardiographic examination; follow-up for subsequent fatal and non-fatal events ended in May 2018. Results: Prevalence of HFpEF (55.21%) is higher than HFrEF (23, 60%) and HFmrEF (17, 19%). Mean age is 80.9 ± 8.3 years, and does not differ among groups. HFpEF are more commonly female, show higher SBP at the presentation (p < 0, 001), and have more non-cardiac comorbidities, such as renal dysfunction (p < 0, 001), anemia (p = 0, 05), chronic obstructive pulmonary disease (p = 0, 036) and also atrial fibrillation (p = 0, 04); in this group hypertensive aetiology is significantly prevailing (p = 0, 002). On the contrary previous myocardial ischaemia and higher NT-proBNP levels on the admission (p = 0, 038) are typical in HFrEF. Diastolic and systolic dysfunctions co-exist in patients and many candidates show marks of inverse remodelling. HFmrEF carry intermediate attributes (prevalence of CAD and systemic multimorbidities) and exhibit a 'hybrid' US hypertrophy pattern (high RWT, medium LVMi); compared to the other groups, they include the lowest trend on NYHA classification (classes I-II, p = 0, 027), a less aggressive treatment with the shortest number of drugs and the shortest dosages (p = 0, 04) and show decreased mortality and rehospitalization rates. During the follow-up, patients with HFmrEF experience more longitudinal transition among groups (33% becomes HFpEF and 23% HFrEF). Figure. No caption available. Conclusions: HFmrEF share features of both HFrEF and HFpEF, with a high prevalence of hypertension and a large longitudinal transition to the other two classes.